THE IDENTITY OF JAVANESE WOMEN (The study of Phenomenology Toward Indonesian Migrant Women Workers) - Anam Miftakhul Huda (Universitas Islam Balitar, 2016)
The woman stands for Java language (wani ditoto) term used for Homo sapiens gender and has reproduction. The opposite sex from the woman is a man or a male. The woman is a word commonly used to describe mature women. Awareness of Indonesian women to work very large, although the country must work out to become migrant workers, this is shown by the increasing number of women migrant workers every year.Based BNP2TKI report in 2013 the number of migrants reached 512 168 people, consisting of 285 197 person formal workers (56 %) and 226 871 informal migrant workers (44 %). Whereas in 2012 migrant workers reached 494 609 people consisting of 258 411 formal sector (52 %) and 236 198 informal migrant workers (48 %). (detik.com). This research using phenomenology approach by deep interview (unstructured) observation non participants and study documentation. The subject in this research is Javanese Indonesian women. The informants of this research are six women workers. The purpose of this research is expected to describe the shift in the concept of Javanese women carry out tasks in abroad, there are Indonesian cultural values implied by the instincts of a typical traditional Javanese woman, though the housemaids are located in other countries.Social identity theory is a theory that was originally engaged in the area of Social Psychology, with the language and its ability to find and understand the meaning, has become a meta - theory that is able to bring together many disciplines such as psychology, anthropology, sociology, history, communications, as implications is that reality is always social, and the social contextual character always in a state of local culture and history.The meaning of something can be very different in cultures or groups of people who are different because in each cultural or community groups have own ways to interpret things. Groups of people who have a background of understanding is not the same to certain cultural codes will not be able to understand the meaning produced by other community groups.Research described that diversity nations woman patriarchy, Javanese culture properties characteristic of java women clearly reflected in life with workers Indonesia (TKW) is different from another country.